The Influence of Organizational Culture, Educational Background and Compensation on Employee Performance at National Sharia Bank - Yoesoep Edhie Rachmad; Faisal Abubakar; Ilham Arief; Sri Hartati; Desi Kristanti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to experimentally examine how educational background and organizational culture affect compensation and how it affects the performance of employees of Islamic Banks. The study makes use of primary data in the form of surveys given to staff members of Islamic banks. The analytical approach in this quantitative study is Patriall Least Square (PLS)-SEM, which uses the SmartPLS 3.0 data analysis tool. According to the study's findings, education has no bearing on characteristics related to pay and performance. Employee performance and compensation are positively and significantly impacted by organizational culture. Employee performance characteristics are significantly and favorably impacted by compensation. There is no compensation-related indirect impact of educational characteristics on employee performance. Organizational culture can have a favorable and considerable impact on employee performance as measured by compensation. The result of this study is the creation of references pertaining to elements that influence worker performance and reduce issues with human resource management in Islamic banking.